Morphological and Transcriptional Responses to CRISPRi Knockdown of Essential Genes in Escherichia coli - Melanie R. Silvis (American Society for Microbiology, 2021)
Essential genes make up only ∼5 to 10% of the genetic complement in most organisms but occupy much of their protein synthesis and account for almost all antibiotic targets. Despite the importance of essential genes, their intractability has, until recently, hampered efforts to study them.